A longitudinal analysis of e-cigarette use and cigar, little cigar or cigarillo initiation among youth and youth adults: 2017–2019. (1st September 2021) - Hair, Elizabeth C.; Kreslake, Jennifer M.; Mowery, Paul; Pitzer, Lindsay; Schillo, Barbara; Vallone, Donna M.
Highlights: E-cigarette use predicts initaition of cigar, little cigar or cigarillo use. The odds of youth and young adults who had ever used JUUL or other e-cigarettes going on to use cigars, little cigars or cigarillos was more than three times greater compared to never users of e-cigarettes. Restrictions on cigars, little cigars or cigarillos should be considered in conjunction with policies designed to reduce the youth e-cigarette use. Abstract: Purpose: To examine whether youth and young adult e-cigarette use is associated with initiation of cigars, little cigars, or cigarillos (CLCCs) and current use of flavored CLCCs. Basic procedures: The sample is drawn from the Truth Longitudinal Cohort, a probability-based longitudinal cohort of youth and young adults recruited at ages 15–21 and surveyed every six months. The sample for this study was CLCC-naïve defined as those who had never used CLCCs as of 2017 (N = 5586). The outcomes were the odds of (1) initiating any CLCC use and (2) reporting current (past 30-day) use of flavored CLCCs from 2018 to late 2019. The main predictor was use of e-cigarettes by 2018. Results: The odds of initiating a CLCC was greater for those who had used ever used JUUL (OR: 3.30, p < 0.001) or were current users of another type of e-cigarette by 2018 (OR: 3.57, p < 0.001). Odds of CLCC initiation was also greater for those who had ever used combustible cigarettes (OR: 1.62, p < 0.05), were current smokers (OR: 3.12, p < 0.001) or had used marijuana (OR: 1.92, p < 0.001) by 2018. E-cigarette use that occurred by 2018 was associated with greater odds of current use of flavored CLCCs compared to non-flavored CLCCs (ever users of JUUL: OR: 2.57, p < 0.01; current users of some other e-cigarette: OR: 3.06, p < 0.05). Conclusion and relevance: This study raises new concerns about the effects of e-cigarette use on subsequent combustible tobacco use. Restrictions on CLCCs should be considered in conjunction with current policies designed to reduce the youth vaping epidemic.